International encyclopedia of composites (VCH, 1990)
This 6-volume series is the only true encyclopedia on composite materials and related process technology. It is comprehensive, containing 250 articles on keywords ranging from ceramic metal-matrix and thermoplastic composites to composite engineering material. It is up-to-date, covering such hot topics as superconducting composites and stealth technology. The series is a combination of expertise, unparalleled in scope. The contributors came from such significant institutions as Boeing, Dupont, Ford, ICI, MIT and NASA. All the background information in the field is provided by this unique reference work.